Tożsamość narodowa Szkotów w Zjednoczonym Królestwie Wielkiej Brytanii i Irlandii Północnej (Politeja, 2019)
Scottish National Identity in the United Kingdom of Great Britain and Northern IrelandScotland became part of the United Kingdom in 1707, when the Act of Union was signed by both the Scottish and English Parliaments. Even though Scots were then largely subordinated to the decisions taken by Westminster, they maintained a sense of independence. One of the most important elements of building Scottish national identity is their history, mainly based on Anglo-Scottish relations and traditions that have been thought to be “invented” by intellectual elites in the eighteenth and nineteenth centuries. The aim of the article is to present Scottish national identity in comparison to historical conditions, with particular emphasis on relations between England and Scotland.